Hidden Hunger, its causes and impact on Human life - Mehboob, Riffat (Pakistan Journal of Health Sciences, 2022)
The term "hidden hunger" refers to an important vitamin and mineral shortage in humans that generally goes unnoticed by the telltale signs and symptoms of micronutrient deficiency illnesses. Hidden hunger is caused by micronutrient deficiency including vitamins and minerals such as vitamin D, vitamin B12, iron, iodine, and zinc. Deficits in vitamins and minerals affect 2 billion individuals worldwide (1). Low-income households frequently lack foods that contain sufficient amounts of vitamin A, iodine, iron, and occasionally other crucial nutrients. This restricts their ability to grow, develop, maintain good health, and work. Making sure people receive the necessary vitamins, minerals, and nutrients can help avoid undernutrition. Essential vitamins and minerals have a long history of discovery, and significant progress has been achieved in the prevention and treatment of linked classic deficiency illnesses (e.g., rickets, scurvy, and anemia). The possibility that an insufficient intake of micronutrients might have negative health effects even in the absence of overt illness symptoms has just lately come to light. From conception through the end of the second year of life, there is a 1,000-day window that is extremely important for growth and development and necessitates an appropriate intake of micronutrients. The concealed hunger brought on by a vitamin shortage does not result in actual hunger. Although you might not feel it in your stomach, it directly affects your health and vigor. The Lancet study (2), observed three key micronutrients i.e., vitamin A, zinc, and iron in 22 countries between the time period of 2003-2019. At least one of these nutrients was deficient globally in 372 million children aged 3 and 1.2 billion women of reproductive age. Three-quarters of these under-nutritioned children were present geographically in Africa, South Asia, and the Pacific and 57% of these women were from east and south Asia and The Pacific. Surprisingly, high income countries also had high prevalence of Hidden Hunger. This may be due to processed foods poor in micronutrients. The 2018 National Nutritional Survey (NNS) report (3) shows that Pakistan faces a triple burden of malnutrition with micronutrient deficiencies, under-nutrition, and obesity coexisting in its’s population. Pakistan has had long-running programs to fortify cooking oil, ghee, and wheat with vitamins. Despite these programs, levels of vitamin A and vitamin D deficits and severe iodine deficiency have risen since the last survey. The fundamental factors causing food insecurity and a poor diet, poverty and a lack of understanding of the value of nutritional diversification. Micronutrients need also increase in certain stages of life such as lactation, pregnancy and in various health conditions such as parasites, infections or diseases. Low absorption of micronutrients although they are consumed in right quantity also remains a major cause. Hidden hunger during pregnancy causes intrauterine growth restriction, which has an impact on the child’s development. Deficiency of Iron causes low energy, low birthweight, anemia, impaired brain development and increased maternal mortality. Vitamin A deficiency causes blindness or visual impairment, infections such as diarrhea and increased danger of ailment and death. Zinc deficiency causes repeating infections and impaired immune system. Iodine deficiency causes goiter, retarded mental capacity and damages in brain of newborn. Hidden hunger is a prevalent problem, affecting people everywhere in the world and more severely in low-income countries like Pakistan.